The weak π − π interaction originated resonant tunneling and fast switching in the carbon based electronic devices - He, Jun (2013)
By means of the nonequilibrium Green's functions and the density functional theory, we have investigated the electronic transport properties of C60 based electronic device with different intermolecular interactions. It is found that the electronic transport properties vary with the types of the interaction between two C60 molecules. A fast electrical switching behavior based on negative differential resistance has been found when two molecules are coupled by the weak π − π interaction. Compared to the solid bonding, the weak interaction is found to induce resonant tunneling, which is responsible for the fast response to the applied electric field and hence the velocity of switching.